Verba Volant, Scripta Manent: The Discontinuity Effect of Explicit Media. - Venturini, Tommaso (American Behavioral Scientist, 2007)
Part of a special issue on the determinants of innovation generation and social change. The writer discusses the existence of a linkage between social patterns and innovation types that depends on the nature of the media available to different groups. Explicitness plays the key role in this linkage. As communities are relatively homogeneous, they can rely on implicit forms of communication; in contrast networks must rely on explicit channels and languages to relate highly diverse components. This difference means that communities and networks are prone to generating linear and radical innovation, respectively.